GG-08 Immune repertoire and genetic risk alleles in healthy pediatric populations with autoimmune indicators. (August 2018) - Raj, Prithvi; Pichilingue-Reto, Patricia; Dozmorov, Igor; Song, Ran; Liang, Chaoying; Arana, Carlos; Cantarel, Brandi; Kim, Daehwan; Zhang, Bo; Zhou, JinChun; Molina, Erika; Gregersen, Peter K; et al.
Abstract : Background: The antibody specificities of an infant progressively form in response to infections, environmental exposures, and vaccinations. While many adults develop antibodies to self-antigens, it remains unknown if these are present in infants and toddlers. Methods: Serum, peripheral blood, and clinical data have been collected from 102 healthy children (1–2 year of age). ANA titers were measured by QuantiaLite ELISA (Inova) and reactivity to 125 diverse autoantigens tested by autoantibody array. Targeted sequencing was performed in 60 children to capture HLA alleles and potentially pathogenic genetic variations in 100 plus loci that are implicated in various autoimmune, rheumatic and immune system related diseases. Sequencing libraries were made using KAPA Biosystems kits. Custom target oligos were synthesized from Nimblegen. Deep sequencing was performed using Illumina HiSeq 4000 platform. Sequencing reads were aligned to reference genome and variants were called using GATK Pipeline. Secondary data analysis is done using Metlab, GraphPad Prism, Haploview and Golden Helix programs. Results: Approximately 28% of very young children have moderate to high-titer autoantibodies, similar to adults, however, no female gender bias was observed. Significant differences between the child and adult immune repertoires were seen. Some samples demonstrated strong signatures of non-nuclear antigens reactivities. Interestingly, the ANA positive group of children exhibited significantly high titers of anti-alpha fodrin IgG (p=0.01), an autoantibody reported in juvenile Sjogren's syndrome. Analysis of sequencing data identified regulatory polymorphisms in HLA class II and III regions that were associated with ANA positivity. About 8% of the ANA positive children also carried autoimmune disease associated HLA-DR-DQ alleles. HLA alleles and regulatory haplotypes were analyzed in relation to various clinical features in children. Serum C4 level measured in subset of ANA positive children identified few with reduced expression. Conclusions: While the immune repertoire of very young children is typically thought of as naïve and self-tolerant, a significant fraction of very young children makes autoantibodies as detected by commercial ANA ELISA and autoantigen arrays. This supports the conclusion that ANA and other autoantibodies are consequences of general body development and immune upregulation and not markers of pathology. One of the major genetic determinants of 'pre-clinical' autoimmunity as measured by ANA is the human major histocompatibility locus, HLA . Within HLA, several 'endophenotypes' emerge, including expression of a complement protein involved in immune complex removal, as well as multiple proteins associated with antigen presentation, including MHC class II. These findings support the idea that there is quantifiable genetic risk for the development of autoimmunity that can be measured in very young individuals.